Risk assessment and control of agricultural supply chains under Internet of Things. Issue 1 (2nd January 2017) - Yan, Bo; Wang, Xinni; Shi, Ping
ABSTRACT: The Internet of Things (IoT) has enhanced the value of agricultural supply chains and reduced traditional risks. However, new risks to the agricultural supply chain have emerged in the IoT era. The risks in the agricultural supply chain under IoT, including risks related to perception, network, and application layers, are summarised in this paper. The ordered weighted averaging operator is utilised to quantitatively evaluate and sort these risks. Subsequently, the supply chain risk diffusion convergence model is used to identify the quantitative indicators that can measure risk fluctuations in the agricultural supply chain according to the risk assessment results. Finally, measures for risk management are proposed according to the results derived through the quantitative model for the agricultural supply chain under IoT.